KEMITRAAN MASYARAKAT DAN STRATEGI PEMASARAN BATIK KELOMPOK PEMBATIK PALBATU - Januarko, Moehammad Unggul (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
AbstractThe Community Service Team met with partners during a situation analysis through interviews in January 2019 to capture the problems faced by partners. The problems are not ready with business risk, can't design batik, don't know entrepreneurial theory, marketing management, can't sew culottes. Based on previous research (Kusumawati, 2017) it was found that the Palbatu batik group had sufficient intentions for entrepreneurship. Partners are slow to sell their batik products so that the capital is stopped, waiting for the batik to be sold. Both partners had difficulty designing a variety of Palbatu batik. The three partners have not yet made sales promotions through the internet so that batik production is known to the public. For this reason, the community service team aims to help partners manage the marketing of the batik industry. The method of implementation is through training, hands-on practice and discussion. Training for partners to improve their batik designs so that batik patterns are attractive and preferred by customers. Equipping risk management knowledge, marketing knowledge, entrepreneurship motivation and entrepreneurship so that batik makers have the skills to design batik. The results of the activities of the Palbatu batik ladies group numbered 10 people and they were enthusiastic about receiving knowledge and practice of designing batik and making culottes pants. The suggestions of women are still painstaking and practice science in order to become successful entrepreneurs. Main outputs of the National Journal of Community Service, special outcomes (1) Batik makers in Palbatu are expected to have knowledge about batik design, batik marketing can foster relationships with customers. (2) Train batik group partners by practicing culottes and sewing patterns. Keywords: Community Partnership, Batik Marketing Strategy Palbatu Batik Group AbstrakTim Pengabdian masyarakat bertemu dengan mitra pada saat analisa situasi melalui wawancara pada bulan Januari 2019 untuk menangkap masalah yang dihadapi mitra. Masalah yang ada belum siap dengan resiko bisnis, belum bisa mendesain batik, belum tau teori wirausaha, manajemen pemasaran, belum bisa menjahit celana kulot. Berdasarkan penelitian terdahulu (Kusumawati, 2017) ditemukan kelompok pembatik Palbatu memiliki niat yang cukup untuk berwirausaha. Mitra lambat menjual hasil batiknya sehingga modal terhenti, menunggu batik terjual. Kedua mitra mengalami kesulitan mendesain aneka ragam batik Palbatu. Ketiga mitra belum melakukan promosi penjualan melalui internet agar produksi batik dikenal masyarakat. Untuk itu tim pengabdian masyarakat bertujuan membantu mitra agar dapat mengelola pemasaran industri batik. Metode pelaksanaan melalui pelatihan, praktek langsung dan diskusi. Pelatihan agar mitra meningkatkan desain batik agar corak batik menarik dan disukai pelanggan. Membekali pengetahuan manajemen resiko, pengetahuan pemasaran, motivasi berwirausaha dan kewirausahaan agar pembatik memiliki ketrampilan mendesain batik. Hasil kegiatan kelompok ibu-ibu pembatik Palbatu berjumlah 10 orang dan mereka antusias menerima pengetahuan dan praktek mendesain batik dan membuat celana kulot. Saran-saran ibu-ibu tetep telaten dan mempraktekkan ilmu pengetahuan agar berhasil menjadi wirausaha. Luaran utama Publikasi Jurnal Nasional Pengmas, luaran khusus (1) Pembatik Palbatu diharapkan memiliki pengetahuan tentang desain batik, pemasaran batik dapat membina hubungan dengan pelanggan. (2) Melatih Mitra kelompok pembatik dengan praktek membuat pola kulot dan menjahit. Kata Kunci: Kemitraan Masyarakat, Strategi Pemasaran Batik Kelompok Pembatik Palbatu